BASIC METHODS OF TRANSLATING AND TRANSFERRING ABBREVIATIONS FROM ENGLISH INTO UZBEK - Ashurova Hafiza; Iskanova Nasiba (TADQIQOTLAR.UZ, 2024)
According to experts, abbreviation should, on a general basis, obey the rules of translation of vocabulary, which are based on semantic correspondences between the correlative units of a given pair of languages, proximity to terms, i.e. the lack of connotations further brings to the fore the need to convey the semantic side of abbreviations. Strictly schematic, word II 1. translated - its content is transmitted by appropriate means of PL (equivalents, analogues) or 2. transferred to the TL text as is, preserving partially or completely the form (borrowing, transcription, transliteration). But an abbreviation is a special word, different from others. Just as a shorthand sign is a representative, a substitute for an ordinary word, so an abbreviation represents another unit potentially contained in it, the original one, from the “fragments” of which it is composed. It is this most important moment of the dual unity of abbreviations (the abbreviated form and the full, expanded original form with the same content) that doubles the possibility of transferring them to TL. Let's imagine this in diagram form: I. Translation 1) in abbreviation, 2) in expanded form. II. Transcription/transliteration of 1) an abbreviation, 2) its expanded form.